The Protective Effect of Cx43 Protein-Mediated Phosphocreatine on Myocardial Ischemia/Reperfusion Injury. (23rd January 2021) - Wang, Chen-xi; Guo, Jun-jun; Di, An-jie; Zhu, Yu; Han, Wei-min; Cheng, An-ran; Li, Cheng; Si, Rui-chan; Lan, Tian-shu; Zhang, Ran; Liu, Hong-li; Yan, Guo-liang
Abstract : Objectives . To verify the protective effect of phosphocreatine on myocardium in an ischemic model and the possible mechanism of action. Methods . The model of myocardial ischemia/reperfusion (I/R) was established by the ligation balloon method. 30 SD rats were randomly divided into three groups, n = 10 in each group. Sham operation group: the coronary artery was not blocked and observed for 120 minutes. The ischemia/reperfusion ( I / R ) group was given ischemia for 30 minutes and ischemia reperfusion for 90 minutes. Phosphocreatine (PCr) group: after 30 minutes of ischemia, the rats were intraperitoneally injected with PCr (200 mg/kg) for 90 minutes. The animal groups of myocardial ischemia/reperfusion model in vitro were the same as those in vivo. The heart was removed by thoracotomy and washed immediately in H-K buffer solution. Then, the heart was installed on the Langendorff instrument. The concentration of PCr perfusion fluid in the PCr group was 10 mmol/L. The changes in coronary blood flow in isolated myocardium were recorded. The heart rate and electrocardiogram were recorded by RM6240BT. At the end of the experiment, myocardial pathological sections and Cx43 immunofluorescence staining were made, and the contents of malondialdehyde (MDA) in myocardial tissue were detected. Results . Phosphocreatinine treatment improved the myocardial ischemia model, performance in electrocardiogram (ECG) changes (ST segment apparent), and histological changes (decrease in necrotic myocardial cells, inflammatory cell infiltration, and a reduction in myocardial edema). At the same time, MDA decreased, while coronary blood flow and Cx43 expression significantly improved. Conclusions . Phosphocreatine can improve the electrocardiogram and restore histologic changes in ischemic myocardium and coronary blood flow. The postulated mechanism is by inhibiting the generation of free oxygen radicals and restoring the expression of Cx43 protein.